FROM DECLARATIONS TO THE REALIZATION OF WOMEN’S PARTICIPATION IN POLITICAL LIFE.GENDER AUDIT - Гнилицька, Анастасія; Михайлюк, Олена (SWorldJournal, 2024)
The article examines to what extent the principles of gender equality are embodied in the work of political structures in Europe and Ukraine, and the gender aspects of the implementation of strategic and program documents and materials related to the fie